Empowerment of the Besi Sora Women Farmers Group through Increasing the Added Value of the Gadung Tuber Industry (Dioscorea Hispida) - Rahmawati, Fitri; Sofyan, Ahdi Topan; Apriani, Ari; Larasati, Depi; Latipa, Latipa; Abidin, Zaenal (Unram Journal of Community Service, 2024)
The skills in making Ngalit gadung sticks are very important for those who want to increase their knowledge to be more creative and innovative in making various types of modern cakes. Ngalit gadung sticks made from gadung are currently one of the modern cakes sold in Beru Village, Jereweh District, West Sumbawa Regency, they have a variety of delicious flavors and the process of making them is easy. Someone's skills in making easy and delicious cakes can be used as a business opportunity to help increase family income. For someone who has large capital, they can open a cake shop so they can improve their family's welfare level. Nowadays, there are many types of modern cakes, so they are required to be more creative and innovative in making cakes. Specific goals the training on making Gadung Ngalit Sticks aims to increase the skills possessed by the community, especially women from the MSME Group, in making cakes made from Gadung raw materials and Participants in this training program know what Gadung Ngalit Sticks are, what the ingredients are, and how to make them. The results to be achieved in implementing the Community Partnership program activities involving several students "Empowering the Besi Sora Women Farming Group (KWT) through increasing the Value Added Gadung Tuber Industry (Dioscorea Hispida)" in Beru Village, Jereweh District, West Sumbawa Regency are for the community, especially mothers. - MSME Group mothers can find out what Gadung Ngalit Stick Cake is and how to make it